Hydrogel adhesive for ophthalmology department and application of hydrogel adhesive

By developing a hydrogel adhesive composited from hydrophilic polymer and block polymer, the shortcomings of existing ophthalmic adhesive materials in ophthalmic applications have been solved, and rapid curing, low swelling, high transparency and Long-term stability meets the high requirements of ophthalmic surgery and reduces postoperative complications.

CN119424718APending Publication Date: 2025-02-14DALIAN UNIV OF TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411609863.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

In ophthalmic tissue adhesive materials, existing ophthalmic tissue adhesive materials have problems such as long curing time, insufficient strength, easy to brittle in the body fluid environment, and the heat released during the curing process may have an adverse effect on the eye tissue, resulting in irritation or damage.

Method used

Develop a hydrogel adhesive for ophthalmics that can be crosslinked in situ, low swelling and high transparency, mainly composed of hydrophilic polymers and block polymers, which can be illuminated by specific end group modifications or It can cure quickly under the action of chemical initiators to ensure a dense and uniform adhesive layer on the wound surface.

Benefits of technology

It achieves rapid curing, low swelling, high transparency and long-term stability, meets the high requirements for accuracy and biocompatibility of ophthalmic surgery, reduces the occurrence of postoperative complications, and provides a more comfortable postoperative experience.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119424718A_ABST
    Figure CN119424718A_ABST
Patent Text Reader

Abstract

The invention discloses an ophthalmic hydrogel adhesive and application thereof, and belongs to the technical field of tissue adhesives. The ophthalmic hydrogel adhesive capable of in-situ rapid crosslinking, low swelling and high transparency is mainly formed by compounding a hydrophilic polymer and a block polymer, the mass ratio of the hydrophilic polymer to the block polymer is (1: 5)-(5: 1), and the hydrophilic polymer is selected from one of polyethylene glycol and polyvinyl alcohol; the block polymer is poloxamer; the end groups of the hydrophilic polymer and the block polymer are modified with cross-linking groups and are covalently connected by the cross-linking groups. The hydrogel adhesive product for the ophthalmology department has excellent biocompatibility, low swelling property, strong adhesiveness and good air permeability, the post-operation tissue repair effect is remarkably improved, postoperative complications are reduced, more comfortable postoperative experience is brought to ophthalmologic operation patients, and the hydrogel adhesive product has remarkable economic benefits and social benefits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of tissue adhesives, and in particular relates to an eye tissue adhesive which can be cross-linked and bonded in situ, has low swelling and is highly transparent. Background Art

[0002] In the field of ophthalmology, tissue adhesives have gradually played an important role in wound repair, surgical suture replacement, and implant fixation. In traditional ophthalmic surgery, suturing technology is usually used to close wounds and fix tissues. However, due to the special physiological structure of ocular tissue and its high demand for minimally invasive and non-destructive operations, suturing surgery is not only complicated and time-consuming, but may also cause mechanical damage to fragile ocular tissues, leading to postoperative pain, inflammatory reactions, and scar formation. For this reason, the development of ophthalmic adhesive materials that are easy to operate and have excellent sealing effects is of great significance in clinical applications.

[0003] At present, clinical ophthalmic tissue adhesive materials mainly include fibrin glue, cyanoacrylate glue, etc. However, existing materials have limitations in ophthalmic applications. Fibrin glue usually has the defects of relatively long curing time and insufficient strength, which is difficult to meet the needs of ophthalmic surgery (WD Spotnitz, World J. Surg. 2010, 34, 632-634.). In addition, cyanoacrylate glue is widely used in various surgical operations due to its strong adhesion, but it is brittle in body fluid environment, and the heat released during curing may have an adverse effect on eye tissue, causing irritation or damage. The degradation products of cyanoacrylate are acidic and easily lead to inflammatory reactions (AJSinger, JV Quinn, JE Hollander, Am. J. Emerg. Med. 2008, 26, 490-496.). Due to the shortcomings of existing commercial ophthalmic tissue adhesive materials, it has become a problem to be solved urgently to develop a special ophthalmic adhesive that can be quickly cured, low swelling, highly transparent, and has long-term stability in a physiological environment. Summary of the invention

[0004] Based on this, the purpose of the present invention is to provide an ophthalmic hydrogel adhesive with in-situ rapid crosslinking, low swelling and high transparency and its application, aiming to overcome the limitations of the prior art. The adhesive material has strong adhesion, adjustable mechanical strength, high transparency and biocompatibility, and can meet the high requirements for precision and biocompatibility in ophthalmic surgery. In addition, the material can also achieve long-term stable adhesion under physiological conditions, avoiding postoperative complications caused by swelling, degradation or mechanical property degradation of the material.

[0005] The object of the present invention is achieved by the following methods:

[0006] The invention provides an ophthalmic hydrogel adhesive which can be rapidly cross-linked in situ, has low swelling and high transparency. The ophthalmic hydrogel adhesive is mainly composed of a hydrophilic polymer and a block polymer, the mass ratio of the hydrophilic polymer to the block polymer is 1:5-5:1, the hydrophilic polymer is selected from one of polyethylene glycol and polyvinyl alcohol; the block polymer is poloxamer; the end groups of the hydrophilic polymer and the block polymer are both modified with cross-linking groups, and are covalently connected by the cross-linking groups, wherein the hydrophilic polymer has good affinity with tissues and has a deeper penetration depth into the tissues, the block polymer with a hydrophobic segment can reduce swelling, and selecting a high molecular weight block polymer as an adhesive can provide more energy dissipation, and the combination of the hydrophilic polymer and the block polymer can significantly prolong the bonding time of the tissues.

[0007] Based on the above technical solution, further, the volume percentage of the polymer in the ophthalmic hydrogel adhesive is 1%-30%, preferably 5%-20%.

[0008] Based on the above technical solution, further, the transmittance of the ophthalmic hydrogel adhesive is 80-100%, the viscosity of the pre-polymerized solution of the ophthalmic hydrogel adhesive is not higher than 60mPa.s, and the penetration depth in the skin tissue is not less than 100μm; the tissue bonding strength of the ophthalmic hydrogel adhesive after curing is 150-300kPa to ensure sufficient wound bonding effect and durability, and the volume swelling rate is less than 40%.

[0009] Based on the above technical solution, further, the cross-linking group includes acrylate, methacrylate, and allyl isocyanate, and the cross-linking of the hydrophilic polymer and the block polymer is achieved through free radical polymerization.

[0010] Based on the above technical solution, further, the mass ratio of the hydrophilic polymer to the block polymer is 3:7 to 7:3.

[0011] Based on the above technical solution, further, the molecular weight of the polyethylene glycol is 0.2kDa-6kDa, preferably 0.2kDa, 2kDa, 4kDa and 6kDa; the molecular weight of the polyvinyl alcohol is 2kDa-75kDa.

[0012] Based on the above technical solution, further, the poloxamer is one of F127, F108, F88, F68, and F87, and has a molecular weight of 1 kDa-30 kDa.

[0013] Based on the above technical scheme, further, the preparation process of the ophthalmic hydrogel adhesive is: by dissolving a hydrophilic polymer modified with a cross-linking group on the end group and a block polymer modified with a cross-linking group on the end group in an aqueous solution to obtain a polymer aqueous solution with a concentration of 5-30wt%, and cross-linking is induced by light or chemical initiator.

[0014] Based on the above technical solution, further, the conditions for photoinduced crosslinking are that the photoinduced wavelength range is 360-405nm and the light intensity is 10-500mW / cm 2 , time 5-200s.

[0015] Based on the above technical solution, further, the chemical initiator includes ammonium persulfate and tetramethylethylenediamine.

[0016] Another aspect of the present invention provides a method for using the above-mentioned ophthalmic hydrogel adhesive, comprising the following steps:

[0017] (1) dissolving a hydrophilic polymer having a cross-linking group modified at its terminal group and a block polymer having a cross-linking group modified at its terminal group in an aqueous solution to obtain a 1-50 wt % polymer aqueous solution;

[0018] (2) When the polymerization is initiated by light-induced crosslinking, a photoinitiator is added to a polymer aqueous solution and mixed evenly to obtain a prepolymer solution. The prepolymer solution is applied to the surface of the tissue to be bonded, and the prepolymer solution is irradiated with light to initiate a crosslinking reaction of the polymer and then solidify, thereby achieving stable adhesion of the tissue;

[0019] When the initiation polymerization method is chemical cross-linking, a chemical initiator is added to the polymer aqueous solution and mixed evenly to obtain a pre-polymer solution, and the pre-polymer solution is applied to the surface of the tissue to be bonded, and then the polymer in the polymer solution is allowed to cross-link and solidify for 10s-200min to achieve stable adhesion of the tissue;

[0020] Based on the above technical solution, further, the concentration of the polymer aqueous solution in step (1) is 5-50wt%, preferably 5-30wt%.

[0021] Based on the above technical solution, further, the photoinitiator described in step (2) includes lithium phenyl-2,4,6-trimethylbenzoylphosphinate, and the light-induced wavelength range is 200-700nm.

[0022] Based on the above technical solution, further, the conditions for the photoinduced polymerization reaction in step (2) are that the photoinduced wavelength range is 360-405nm and the light intensity is 10-500mW / cm 2 , time 5-200s.

[0023] Based on the above technical solution, further, the chemical initiator described in step (2) includes ammonium persulfate and tetramethylethylenediamine.

[0024] The present invention also provides the use of the above-mentioned ophthalmic hydrogel adhesive as a highly transparent ophthalmic tissue adhesive in ocular surface surgery.

[0025] Based on the above technical solution, further, the ocular surface surgery includes conjunctival trauma / transplantation adhesion, corneal trauma / transplantation adhesion, retinal trauma / transplantation adhesion, and ocular surface trauma closure.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] 1. The ophthalmic hydrogel adhesive material of the present invention utilizes a unique combination of short-chain hydrophilic polymers and block copolymers, and can be rapidly cured under light or chemical initiators through specific end group modification. Through the introduction of end group modification groups (such as acrylates, epoxy groups, etc.), the material can achieve rapid free radical polymerization under low-energy light sources, thereby forming a dense and uniform adhesive layer on the wound surface. At the same time, the combination of block copolymers and short-chain hydrophilic polymers significantly improves the elasticity and flexibility of the material, allowing it to adapt to slight deformations of eyeball tissues and reduce foreign body sensation.

[0028] 2. In order to reduce the swelling of the material, the present invention precisely controls the hydrophilicity and cross-linking density of the polymer, so that it maintains low swelling characteristics in the intraocular environment and prevents excessive expansion from having adverse effects on eye tissues. The high air permeability of the material also ensures normal oxygen exchange of eye tissues, reducing the risk of postoperative hypoxia and infection. In addition, the mechanical strength of the material can be finely adjusted by regulating the molecular weight and cross-linking density of the polymer chain to ensure that it can provide sufficient tissue support without compressing or damaging the fragile eye tissues.

[0029] 3. The ophthalmic hydrogel adhesive material of the present invention is not only suitable for wound sealing in operations such as corneal lacerations and retinal repair, but can also be used as a fixative for implants (such as artificial lenses), providing a new solution for minimally invasive ophthalmic surgery; its long-term stability in a physiological environment makes it an ideal choice for complex operations such as corneal transplantation and ocular trauma repair; in addition, the material can be further used for wound sealing of other mucosa and soft tissues through formula optimization, and has broad clinical application prospects.

[0030] 4. The ophthalmic hydrogel adhesive product of the present invention has excellent biocompatibility, low swelling, strong adhesion and good air permeability, which significantly improves the effect of postoperative tissue repair and reduces the occurrence of postoperative complications, bringing a more comfortable postoperative experience to ophthalmic surgery patients, and has significant economic and social benefits. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] In order to more clearly illustrate the embodiments of the present invention, the drawings related to the embodiments are briefly introduced below.

[0032] Figure 1 3 is a graph showing the relationship between the curing time and the bonding strength of the hydrogel described in Example 2 of the present invention.

[0033] Figure 2 It is a schematic diagram of the customized burst pressure test of the present invention.

[0034] Figure 3 The following is a comparison of the bonding strengths of the ophthalmic tissue adhesive of Example 2 of the present invention and the commercial adhesive of Comparative Example 4.

[0035] Figure 4 The figure shows the swelling condition of the ophthalmic tissue adhesive of Example 3 of the present invention in PBS.

[0036] Figure 5 This is a cell fluorescence image after culturing cells with the extract of the ophthalmic tissue adhesive of Example 2 of the present invention.

[0037] Figure 6 This is a graph showing the hemolysis rate of the blood compatibility of the ophthalmic tissue adhesive according to Example 2 of the present invention.

[0038] Figure 7 It is a diagram showing the corneal transplantation process and effects of Example 12 of the present invention and Comparative Example 6.

[0039] Figure 8 It is the HE section staining picture of Example 12 of the present invention and Comparative Example 6 7 days after corneal transplantation.

[0040] Fig. 9 It is a diagram of the conjunctival surgery process and effects of Example 13 of the present invention and Comparative Example 7.

[0041] Fig.10 It is the HE section staining picture of Example 13 of the present invention and Comparative Example 7 7 days after conjunctival surgery. DETAILED DESCRIPTION

[0042] Various embodiments and specific implementations will be described in detail below. These embodiments should not be construed as limiting the scope of this patent application in any way, and changes and modifications may be made without departing from the essence and scope of the present invention. In addition, only some end uses are discussed herein, but end uses not specifically described herein are also included in the scope of this application. Therefore, the scope of this patent application should be determined by the claims.

[0043] Example 1

[0044] 10g of polyethylene glycol (PEG) with a molecular weight of 0.6kDa and 2kDa was dissolved in 50mL of anhydrous dichloromethane, and 3.6mL of triethylamine and 2.2mL of acryloyl chloride were added in turn to react in an ice bath for 24 hours. After the reaction was completed, 3g of magnesium carbonate was added, filtered, and then 100mL of water was added for extraction and separation. The obtained organic phase was precipitated in ether, and the precipitate was freeze-dried to obtain photo-crosslinkable PEG (PEGDA).

[0045] 10g of F108 (molecular weight 14.6kDa) was dissolved in 150mL of anhydrous dichloromethane, and 2.4mL of triethylamine and 1.7mL of acryloyl chloride were added in turn to react at room temperature for 24 hours. After the reaction was completed, 2g of magnesium carbonate was added, filtered, and then 100mL of water was added for extraction and separation. The obtained organic phase was precipitated in ether, and the precipitate was freeze-dried to obtain photo-crosslinkable F108 (F108DA).

[0046] Example 2

[0047] 3 g of 0.6 kDa PEGDA and 7 g of F108DA were mixed in 100 mL of aqueous solution and stirred at 25° C. for 1 h to obtain a uniform mixed solution. The viscosity of the solution was tested, and the results are shown in Table 1.

[0048] Add 0.2 g of phenyl-2,4,6-trimethylbenzoyl lithium phosphinate to the mixed solution obtained in Example 2 and mix well. Then take 1 mL and inject it into a silica gel mold. 2 After irradiation under ultraviolet light for 10 seconds, the prepared hydrogel was taken out and immersed in PBS buffer solution at 37°C. After 48 hours, the volume change of the hydrogel was recorded to determine its volume swelling rate. The specific data are shown in Table 1.

[0049] 0.2 g of phenyl-2,4,6-trimethylbenzoyl phosphinate lithium was added to the mixed solution obtained in Example 2 and mixed evenly. Then 200 μL was injected onto the surface of pig skin and the PET backing was covered with 10 mm 2 The area was overlapped on the pig skin and 365nm, 50mW / cm 2 After irradiation under blue ultraviolet light for 10 seconds, the sample was placed on a mechanical testing machine and loaded to failure at a speed of 5 mm / min. The load at failure was recorded and the test overlap was calculated. The specific data are shown in Table 1.

[0050] Fresh pig skin was fixed on the upper surface of a custom-made burst pressure device (device as Figure 2A circular hole with a diameter of 2 mm was created in the center of the pig skin in the device. Thereafter, 500 μL of the prepolymerized solution of Example 2 was injected at the puncture site and illuminated. The measuring device was connected to a syringe pump filled with PBS solution. Finally, the PBS solution was injected into the device, and the maximum burst pressure was recorded using a digital pressure gauge (MIK-Y180, Asmik, China), and the specific data are shown in Table 1.

[0051] 0.2 g of phenyl-2,4,6-trimethylbenzoyl phosphinate lithium was added to the mixed solution obtained in Example 2 and mixed evenly. Then 200 μL was injected onto the surface of pig skin and the PET backing was covered with 10 mm 2 The area was overlapped on the pig skin and 365nm, 50mW / cm 2 After irradiation with blue ultraviolet light for 10 s, the samples were immersed in PBS at 37°C for 3 days and the tissue was observed to determine whether it fell off to determine the long-term adhesion stability.

[0052] Table 1 Prepolymer viscosity prepared in Example 2 and the swelling ratio, bonding strength, bursting pressure of the hydrogel and whether it falls off after immersion

[0053] Viscosity Swelling rate Adhesion strength Burst Pressure Whether it falls off Example 2 80mPa·s 29% 163kPa 102kPa no

[0054] Example 3

[0055] 5 g of 0.6 kDa PEGDA and 5 g of F108DA were mixed in 100 mL of aqueous solution and stirred at 25° C. for 1 h to obtain a uniform mixed solution. The viscosity of the solution was tested, and the results are shown in Table 2.

[0056] Add 0.2 g of phenyl-2,4,6-trimethylbenzoylphosphinate lithium to the mixed solution obtained in Example 3 and mix well. Then take 1 mL and inject it into a silica gel mold and use 365 nm, 50 mW / cm 2 After irradiation under ultraviolet light for 10 seconds, the prepared hydrogel was taken out and immersed in PBS buffer solution at 37°C. After 48 hours, the volume change of the hydrogel was recorded to determine its volume swelling rate. The specific data are shown in Table 2.

[0057] 0.2 g of phenyl-2,4,6-trimethylbenzoyl phosphinate lithium was added to the mixed solution obtained in Example 3 and mixed evenly. Then 200 μL was injected onto the surface of pig skin and the PET backing was covered with 10 mm 2 The area was overlapped on the pig skin and 365nm, 50mW / cm 2 After irradiation under ultraviolet light for 10 seconds, the sample was placed on a mechanical testing machine and loaded to failure at a speed of 5 mm / min. The load at failure was recorded and the test overlap was calculated. The specific data are shown in Table 2.

[0058] Fresh pig skin was fixed on the upper surface of a custom-made burst pressure device (device as Figure 2 A circular hole with a diameter of 2 mm was created in the center of the pig skin in the device. Thereafter, 500 μL of the prepolymerized solution of Example 3 was injected at the puncture site and illuminated. The measuring device was connected to a syringe pump filled with PBS solution. Finally, the PBS solution was injected into the device, and the maximum burst pressure was recorded using a digital pressure gauge (MIK-Y180, Asmik, China), and the specific data are shown in Table 2.

[0059] 0.2 g of phenyl-2,4,6-trimethylbenzoyl phosphinate lithium was added to the mixed solution obtained in Example 3 and mixed evenly. Then 200 μL was injected onto the surface of pig skin and the PET backing was covered with 10 mm 2 The area was overlapped on the pig skin and 365nm, 50mW / cm 2 After irradiation with blue ultraviolet light for 10 s, the samples were immersed in PBS at 37°C for 3 days and the tissue was observed to determine whether it fell off to determine the long-term adhesion stability.

[0060] Table 2 Prepolymer viscosity prepared in Example 3 and the swelling ratio, bonding strength, bursting pressure of the hydrogel and whether it falls off after immersion

[0061] Viscosity Swelling rate Adhesion strength Burst Pressure Whether it falls off Example 3 85mPa·s 35% 203kPa 104kPa no

[0062] Example 4

[0063] 7 g of 0.6 kDa PEGDA and 3 g of F108DA were mixed in 100 mL of aqueous solution and stirred at 25° C. for 1 h to obtain a uniform mixed solution. The viscosity of the solution was tested, and the results are shown in Table 1.

[0064] Add 0.2 g of phenyl-2,4,6-trimethylbenzoylphosphinate lithium to the mixed solution obtained in Example 4 and mix well. Then take 1 mL and inject it into a silica gel mold and use 365 nm, 50 mW / cm 2 After irradiation under ultraviolet light for 10 seconds, the prepared hydrogel was taken out and immersed in PBS buffer solution at 37°C. After 48 hours, the volume change of the hydrogel was recorded to determine its volume swelling rate. The specific data are shown in Table 3.

[0065] 0.2 g of phenyl-2,4,6-trimethylbenzoyl phosphinate lithium was added to the mixed solution obtained in Example 4 and mixed evenly. Then 200 μL was injected onto the surface of pig skin and the PET backing was covered with 10 mm 2 The area was overlapped on the pig skin and 365nm, 50mW / cm 2After irradiation under ultraviolet light for 10 seconds, the sample was placed on a mechanical testing machine and loaded to failure at a speed of 5 mm / min. The load at failure was recorded and the test overlap was calculated. The specific data are shown in Table 3.

[0066] Fresh pig skin was fixed on the upper surface of a custom-made burst pressure device (device as Figure 2 A circular hole with a diameter of 2 mm was created in the center of the pig skin in the device. Thereafter, 500 μL of the prepolymerized solution of Example 4 was injected at the puncture site and illuminated. The measuring device was connected to a syringe pump filled with PBS solution. Finally, the PBS solution was injected into the device, and the maximum burst pressure was recorded using a digital pressure gauge (MIK-Y180, Asmik, China), and the specific data are shown in Table 3.

[0067] 0.2 g of phenyl-2,4,6-trimethylbenzoyl phosphinate lithium was added to the mixed solution obtained in Example 4 and mixed evenly. Then 200 μL was injected onto the surface of pig skin and the PET backing was covered with 10 mm 2 The area was overlapped on the pig skin and 365nm, 50mW / cm 2 After irradiation with blue ultraviolet light for 10 s, the samples were immersed in PBS at 37°C for 3 days and the tissue was observed to determine whether it fell off to determine the long-term adhesion stability.

[0068] Table 3 Prepolymer viscosity prepared in Example 4 and the swelling ratio, adhesive strength, bursting pressure and whether the hydrogel falls off after immersion

[0069] Viscosity Swelling rate Adhesion strength Burst Pressure Whether it falls off Example 4 72mPa·s 36% 199kPa 103kPa no

[0070] Example 5

[0071] 3 g of 2 kDa PEGDA and 7 g of F108DA were mixed in 100 mL of aqueous solution and stirred at 25° C. for 1 h to obtain a uniform mixed solution. The viscosity of the solution was tested, and the results are shown in Table 4.

[0072] 0.2 g of phenyl-2,4,6-trimethylbenzoyl lithium phosphinate was added to the mixed solution obtained in Example 5 and mixed evenly. Then 1 mL was injected into a silica gel mold and heated at 365 nm and 50 mW / cm 2 After irradiation under ultraviolet light for 10 seconds, the prepared hydrogel was taken out and immersed in PBS buffer solution at 37°C. After 48 hours, the volume change of the hydrogel was recorded to determine its volume swelling rate. The specific data are shown in Table 4.

[0073] 0.2 g of phenyl-2,4,6-trimethylbenzoyl phosphinate lithium was added to the mixed solution obtained in Example 5 and mixed evenly. Then 200 μL was injected onto the surface of pig skin and the PET backing was covered with 10 mm2 The area was overlapped on the pig skin and 365nm, 50mW / cm 2 After irradiation under ultraviolet light for 10 seconds, the sample was placed on a mechanical testing machine and loaded to failure at a speed of 5 mm / min. The load at failure was recorded and the test overlap was calculated. The specific data are shown in Table 4.

[0074] Fresh pig skin was fixed on the upper surface of a custom-made burst pressure device (device as Figure 2 A circular hole with a diameter of 2 mm was created in the center of the pig skin in the device. Thereafter, 500 μL of the prepolymerized solution of Example 5 was injected at the puncture site and illuminated. The measuring device was connected to a syringe pump filled with PBS solution. Finally, the PBS solution was injected into the device, and the maximum burst pressure was recorded using a digital pressure gauge (MIK-Y180, Asmik, China), and the specific data are shown in Table 4.

[0075] 0.2 g of phenyl-2,4,6-trimethylbenzoyl phosphinate lithium was added to the mixed solution obtained in Example 5 and mixed evenly. Then 200 μL was injected onto the surface of pig skin and the PET backing was covered with 10 mm 2 The area was overlapped on the pig skin and 365nm, 50mW / cm 2 After irradiation with blue ultraviolet light for 10 s, the samples were immersed in PBS at 37°C for 3 days and the tissue was observed to determine whether it fell off to determine the long-term adhesion stability.

[0076] Table 4 Prepolymer viscosity prepared in Example 5 and the swelling ratio, adhesive strength, bursting pressure and whether the hydrogel falls off after immersion

[0077] Viscosity Swelling rate Adhesion strength Burst Pressure Whether it falls off Example 5 92mPa·s 33% 173kPa 92kPa no

[0078] Example 6

[0079] 5 g of 2 kDa PEGDA and 5 g of F108DA were mixed in 100 mL of aqueous solution and stirred at 25° C. for 1 h to obtain a uniform mixed solution. The viscosity of the solution was tested, and the results are shown in Table 5.

[0080] Add 0.2 g of phenyl-2,4,6-trimethylbenzoylphosphinate lithium to the mixed solution obtained in Example 6 and mix well. Then take 1 mL and inject it into a silica gel mold. 2 After irradiation under ultraviolet light for 10 seconds, the prepared hydrogel was taken out and immersed in PBS buffer solution at 37°C. After 48 hours, the volume change of the hydrogel was recorded to determine its volume swelling rate. The specific data are shown in Table 5.

[0081] 0.2 g of phenyl-2,4,6-trimethylbenzoyl phosphinate lithium was added to the mixed solution obtained in Example 6 and mixed evenly. Then 200 μL was injected onto the surface of pig skin and the PET backing was covered with 10 mm 2 The area was overlapped on the pig skin and 365nm, 50mW / cm 2 After irradiation under ultraviolet light for 10 seconds, the sample was placed on a mechanical testing machine and loaded to failure at a speed of 5 mm / min. The load at failure was recorded and the test overlap was calculated. The specific data are shown in Table 5.

[0082] Fresh pig skin was fixed on the upper surface of a custom-made burst pressure device (device as Figure 2 A circular hole with a diameter of 2 mm was created in the center of the pig skin in the device. Thereafter, 500 μL of the prepolymerized solution of Example 6 was injected at the puncture site and illuminated. The measuring device was connected to a syringe pump filled with PBS solution. Finally, the PBS solution was injected into the device, and the maximum burst pressure was recorded using a digital pressure gauge (MIK-Y180, Asmik, China), and the specific data are shown in Table 5.

[0083] 0.2 g of phenyl-2,4,6-trimethylbenzoyl phosphinate lithium was added to the mixed solution obtained in Example 6 and mixed evenly. Then 200 μL was injected onto the surface of pig skin and the PET backing was covered with 10 mm 2 The area was overlapped on the pig skin and 365nm, 50mW / cm 2 After irradiation with blue ultraviolet light for 10 s, the samples were immersed in PBS at 37°C for 3 days and the tissue was observed to determine whether it fell off to determine the long-term adhesion stability.

[0084] Table 5 Prepolymer viscosity prepared in Example 6 and the swelling ratio, adhesive strength, bursting pressure and whether the hydrogel falls off after immersion

[0085] Viscosity Swelling rate Adhesion strength Burst Pressure Whether it falls off Example 6 87mPa·s 30% 183kPa 92kPa no

[0086] Example 7

[0087] 7 g of 2 kDa PEGDA and 3 g of F108DA were mixed in 100 mL of aqueous solution and stirred at 25° C. for 1 h to obtain a uniform mixed solution. The viscosity of the solution was tested, and the results are shown in Table 6.

[0088] 0.2 g of phenyl-2,4,6-trimethylbenzoyl lithium phosphinate was added to the mixed solution obtained in Example 7 and mixed evenly. Then 1 mL was injected into a silica gel mold and heated at 365 nm and 50 mW / cm 2After irradiation under ultraviolet light for 10 seconds, the prepared hydrogel was taken out and immersed in PBS buffer solution at 37°C. After 48 hours, the volume change of the hydrogel was recorded to determine its volume swelling rate. The specific data are shown in Table 6.

[0089] 0.2 g of phenyl-2,4,6-trimethylbenzoylphosphinate lithium was added to the mixed solution obtained in Example 7 and mixed evenly. Then 200 μL was injected onto the surface of pig skin and the PET backing was covered with 10 mm 2 The area was overlapped on the pig skin and 365nm, 50mW / cm 2 After irradiation under ultraviolet light for 10 seconds, the sample was placed on a mechanical testing machine and loaded to failure at a speed of 5 mm / min. The load at failure was recorded and the test overlap was calculated. The specific data are shown in Table 6.

[0090] Fresh pig skin was fixed on the upper surface of a custom-made burst pressure device (device as Figure 2 A circular hole with a diameter of 2 mm was created in the center of the pig skin in the device. Thereafter, 500 μL of the prepolymerized solution of Example 7 was injected at the puncture site and illuminated. The measuring device was connected to a syringe pump filled with PBS solution. Finally, the PBS solution was injected into the device, and the maximum burst pressure was recorded using a digital pressure gauge (MIK-Y180, Asmik, China), and the specific data are shown in Table 6.

[0091] 0.2 g of phenyl-2,4,6-trimethylbenzoylphosphinate lithium was added to the mixed solution obtained in Example 7 and mixed evenly. Then 200 μL was injected onto the surface of pig skin and the PET backing was covered with 10 mm 2 The area was overlapped on the pig skin and 365nm, 50mW / cm 2 After irradiation with blue ultraviolet light for 10 s, the samples were immersed in PBS at 37°C for 3 days and the tissue was observed to determine whether it fell off to determine the long-term adhesion stability.

[0092] Table 6 Results of the viscosity of the prepolymer solution prepared in Example 7 and the swelling ratio, adhesive strength, bursting pressure and whether the hydrogel falls off after immersion

[0093] Viscosity Swelling rate Adhesion strength Burst Pressure Whether it falls off Example 7 72mPa·s 38% 185kPa 97kPa no

[0094] Comparative Example 1

[0095] 10 g of 0.6 kDa PEGDA was dissolved in 100 mL of aqueous solution and stirred at 25° C. for 1 h to obtain a uniform mixed solution. The viscosity of the solution was tested, and the results are shown in Table 7.

[0096] Add 0.2 g of phenyl-2,4,6-trimethylbenzoylphosphinate lithium to the mixed solution obtained in Comparative Example 1 and mix well. Then take 1 mL and inject it into a silica gel mold. 2 After irradiation under blue ultraviolet light for 10 seconds, the prepared hydrogel was taken out and immersed in PBS buffer solution at 37°C. After 48 hours, the volume change of the hydrogel was recorded to determine its volume swelling rate. The specific data are shown in Table 7.

[0097] 0.2 g of phenyl-2,4,6-trimethylbenzoyl phosphinate lithium was added to the mixed solution obtained in Comparative Example 1 and mixed evenly. Then 200 μL was injected on the surface of pig skin and the PET backing was covered with 10 mm 2 The area was overlapped on the pig skin and 365nm, 50mW / cm 2 After irradiation under ultraviolet light for 10 seconds, the sample was placed on a mechanical testing machine and loaded to failure at a speed of 5 mm / min. The load at failure was recorded and the test overlap was calculated. The specific data are shown in Table 7.

[0098] Fresh pig skin was fixed on the upper surface of a custom-made burst pressure device (device as Figure 2 As shown), a circular hole with a diameter of 2 mm was created in the center of the pig skin in the device. Thereafter, 500 μL of the prepolymerized solution of Comparative Example 1 was injected at the puncture site and illuminated. The measuring device was connected to a syringe pump filled with PBS solution. Finally, the PBS solution was injected into the device, and the maximum burst pressure was recorded using a digital pressure gauge (MIK-Y180, Asmik, China), and the specific data are shown in Table 7.

[0099] 0.2 g of phenyl-2,4,6-trimethylbenzoyl phosphinate lithium was added to the mixed solution obtained in Comparative Example 1 and mixed evenly. Then 200 μL was injected on the surface of pig skin and the PET backing was covered with 10 mm 2 The area was overlapped on the pig skin and 365nm, 50mW / cm 2 After irradiation with blue ultraviolet light for 10 s, the samples were immersed in PBS at 37°C for 3 days and the tissue was observed to determine whether it fell off to determine the long-term adhesion stability.

[0100] Table 7 Prepolymer viscosity prepared in Comparative Example 1 and the swelling rate, adhesive strength, bursting pressure and whether the hydrogel falls off after immersion

[0101] Viscosity Swelling rate Adhesion strength Burst Pressure Whether it falls off Comparative Example 1 56mPa·s 19% 53kPa 22kPa yes

[0102] Comparative Example 2

[0103] 10 g of 2 kDa PEGDA was dissolved in 100 mL of aqueous solution and stirred at 25° C. for 1 h to obtain a uniform mixed solution. The viscosity of the solution was tested, and the results are shown in Table 8.

[0104] Add 0.2 g of phenyl-2,4,6-trimethylbenzoyl phosphinate lithium to the mixed solution obtained in Comparative Example 2 and mix well. Then take 1 mL and inject it into a silica gel mold and use 365 nm, 50 mW / cm 2 After irradiation under blue ultraviolet light for 10 seconds, the prepared hydrogel was taken out and immersed in PBS buffer solution at 37°C. After 48 hours, the volume change of the hydrogel was recorded to determine its volume swelling rate. The specific data are shown in Table 8.

[0105] 0.2 g of phenyl-2,4,6-trimethylbenzoyl phosphinate lithium was added to the mixed solution obtained in Comparative Example 2 and mixed evenly. Then 200 μL was injected onto the surface of pig skin and the PET backing was covered with 10 mm 2 The area was overlapped on the pig skin and 365nm, 50mW / cm 2 After irradiation under blue ultraviolet light for 10 seconds, the sample was placed on a mechanical testing machine and loaded to failure at a speed of 5 mm / min. The load at failure was recorded and the test overlap was calculated. The specific data are shown in Table 8.

[0106] Fresh pig skin was fixed on the upper surface of a custom-made burst pressure device (device as Figure 2 As shown), a circular hole with a diameter of 2 mm was created in the center of the pig skin in the device. Thereafter, 500 μL of the prepolymerized solution of Comparative Example 2 was injected at the puncture site and illuminated. The measuring device was connected to a syringe pump filled with PBS solution. Finally, the PBS solution was injected into the device, and the maximum burst pressure was recorded using a digital pressure gauge (MIK-Y180, Asmik, China), and the specific data are shown in Table 8.

[0107] 0.2 g of phenyl-2,4,6-trimethylbenzoyl phosphinate lithium was added to the mixed solution obtained in Comparative Example 2 and mixed evenly. Then 200 μL was injected onto the surface of pig skin and the PET backing was covered with 10 mm 2 The area was overlapped on the pig skin and 365nm, 50mW / cm 2 After irradiation with blue ultraviolet light for 10 s, the samples were immersed in PBS at 37°C for 3 days and the tissue was observed to determine whether it fell off to determine the long-term adhesion stability.

[0108] Table 8 Prepolymer viscosity prepared in Comparative Example 2 and the swelling rate, adhesive strength, bursting pressure and whether the hydrogel falls off after immersion

[0109] Viscosity Swelling rate Adhesion strength Burst Pressure Whether it falls off Comparative Example 2 76mPa·s 20% 61kPa 26kPa yes

[0110] Comparative Example 3

[0111] 10 g of F108DA was dissolved in 100 mL of aqueous solution and stirred at 25° C. for 1 h to obtain a uniform mixed solution. The viscosity of the solution was tested. The results are shown in Table 9.

[0112] Add 0.2 g of phenyl-2,4,6-trimethylbenzoyl phosphinate lithium to the mixed solution obtained in Comparative Example 3 and mix well. Then take 1 mL and inject it into a silica gel mold and use 365 nm, 50 mW / cm 2 After irradiation under ultraviolet light for 10 seconds, the prepared hydrogel was taken out and immersed in PBS buffer solution at 37°C. After 48 hours, the volume change of the hydrogel was recorded to determine its volume swelling rate. The specific data are shown in Table 9.

[0113] 0.2 g of phenyl-2,4,6-trimethylbenzoyl phosphinate lithium was added to the mixed solution obtained in Comparative Example 3 and mixed evenly. Then 200 μL was injected onto the surface of pig skin and the PET backing was covered with 10 mm 2 The area was overlapped on the pig skin and 365nm, 50mW / cm 2 After irradiation under ultraviolet light for 10 seconds, the sample was placed on a mechanical testing machine and loaded to failure at a speed of 5 mm / min. The load at failure was recorded and the test overlap was calculated. The specific data are shown in Table 9.

[0114] Fresh pig skin was fixed on the upper surface of a custom-made burst pressure device (device as Figure 2 As shown), a circular hole with a diameter of 2 mm was created in the center of the pig skin in the device. Thereafter, 500 μL of the prepolymerized solution of Comparative Example 3 was injected at the puncture site and illuminated. The measuring device was connected to a syringe pump filled with PBS solution. Finally, the PBS solution was injected into the device, and the maximum burst pressure was recorded using a digital pressure gauge (MIK-Y180, Asmik, China), and the specific data are shown in Table 9.

[0115] 0.2 g of phenyl-2,4,6-trimethylbenzoyl phosphinate lithium was added to the mixed solution obtained in Comparative Example 3 and mixed evenly. Then 200 μL was injected onto the surface of pig skin and the PET backing was covered with 10 mm 2 The area was overlapped on the pig skin and 365nm, 50mW / cm 2 After irradiation with blue ultraviolet light for 10 s, the samples were immersed in PBS at 37°C for 3 days and the tissue was observed to determine whether it fell off to determine the long-term adhesion stability.

[0116] Table 9 Prepolymer viscosity prepared in Comparative Example 3 and the swelling rate, adhesive strength, bursting pressure and whether the hydrogel falls off after immersion

[0117] Viscosity Swelling rate Adhesion strength Burst Pressure Whether it falls off Comparative Example 2 536mPa·s 79% 74kPa 35kPa yes

[0118] Comparative Example 4

[0119] The bonding strength of commercial cyanoacrylate (purchased from Ethicon), protein glue (purchased from CryoLife, USA), Coseal (purchased from Baxter, USA) and Duraseal (purchased from Medtronic, USA) on pig skin tissue was tested according to the method of Example 2. The specific method is to inject 200 μL of the commercial adhesive on the surface of pig skin and cover the PET backing with 10 mm 2 After the area of ​​​​the sample was overlapped on the pig skin for 30 seconds, the sample was placed on a mechanical testing machine and loaded at a speed of 5mm / min until the sample was damaged. The load at the time of damage was recorded and the test overlap bond strength was calculated. The results are shown in Figure 3 .

[0120] Example 8 (Transparency Test Experiment)

[0121] Using the hydrogel prepared in Example 2-7, the hydrogel was placed in a specific sample cell (500 μm) of a spectrophotometer. The transmittance of the sample at a wavelength of 600 nm was measured using a spectrophotometer, and the transmittance value was recorded. The closer the transmittance value is to 100%, the higher the transparency.

[0122] Table 10 Hydrogel permeability results

[0123] Transmittance (%) Example 2 93 Example 3 87 Example 4 92 Example 5 83 Example 6 85 Example 7 89

[0124] Comparative Example 5 (Transparency Comparative Example, compared with other adhesives)

[0125] Referring to the method of Example 8, the transmittance of cyanoacrylate (purchased from Beijing Compat Medical Instrument Co., Ltd.) and fibrin glue (purchased from Shanghai Laishi Blood Products Co., Ltd.) at a wavelength of 600 nm was detected. The results are shown in Table 11.

[0126] Table 11 Permeability results of cyanoacrylate and fibrin glue

[0127] Transmittance (%) Cyanoacrylate 52 Fibrin glue 69

[0128] Example 9 (Tissue penetration of prepolymer solution)

[0129] Fluorescent groups were grafted on the surfaces of 0.6kDa, 2kDa polyethylene glycol and Pluronic F108 to observe the penetration ability of the adhesive. The specific fluorescent grafting steps were as follows: 10 grams of 0.6kDa, 2kDa polyethylene glycol and Pluronic F108 were dissolved in 50mL of dichloromethane, 5mL of triethylamine was added, and 4mL of dichloromethane solution of 1 gram of p-toluenesulfonyl chloride was added dropwise under stirring. The addition was completed in 30 minutes. After stirring overnight, it was washed with 1mol / L hydrochloric acid solution, washed three times with water and saturated sodium bicarbonate solution, added with anhydrous magnesium sulfate to dry, and then rotary evaporated, and n-hexane was added for precipitation. After the product was dried, 1 gram was weighed and dissolved in 10mL of water, 10 mg of rhodamine-isothiocyanate was added and stirred for 5 hours, and then extracted with dichloromethane solution. The organic phase was taken and dried with anhydrous magnesium sulfate, rotary evaporated and precipitated with n-hexane.

[0130] Prepolymer solutions of the grafted fluorescent polymers were prepared according to the proportions in Examples 2-7, and 10 μL was added dropwise to the surface of 15% gelatin gel. Using a confocal scanning microscope, the sample was excited at 595 nm and the fluorescence depth was measured. The results are shown in Table 12.

[0131] Table 12 Tissue penetration results of prepolymer solutions prepared in Examples 2-7

[0132] Example 2 3 4 5 6 7 Penetration depth (μm) 135 122 128 112 124 111

[0133] Example 10 (Cytocompatibility)

[0134] The biocompatibility of the adhesive was investigated by in vitro cell culture experiments using the adhesive prepared in the ratio in Example 2. Taking the double network hydrogel in Example 2 as an example, the specific implementation steps are as follows:

[0135] Use ultraviolet light (with a wavelength of 365nm and an intensity of 50mW / cm 2 ) irradiate the adhesive prepolymer solution for 30 seconds to obtain a hydrogel. Subsequently, the gel was immersed in the culture medium for 24 hours to obtain an extract (the material accounted for 20% of the culture medium), which was set aside after completion. Next, L929 cells (from a mouse fibroblast cell line, taken from the ATCC cell bank) were digested with trypsin. After that, the treated cells were placed in a 24-well plate and cultured overnight at a temperature of 37°C and a carbon dioxide concentration of 5%, so that the cells could adhere to the well plate. Then, the culture medium was aspirated and replaced with the previously prepared extract, which was again placed at a temperature of 37°C and a carbon dioxide concentration of 5% and cultured for 24 hours. Finally, the cells in the gel extract were stained using a fluorescent live / dead assay to evaluate the viability of the hydrogel-encapsulated cells. Among them, green fluorescence represents live cells, and red fluorescence represents dead cells.

[0136] The results are as follows Figure 5 As shown, from Figure 5 From the presented results, it can be confirmed that the adhesive has good biocompatibility.

[0137] Example 11 (Blood Compatibility)

[0138] First, 5 mL of blood was collected from the rabbit ear and stored in an environment of 4°C. After that, 1 mL of anticoagulated blood was added to 2 mL of saline and mixed evenly by shaking to achieve the purpose of diluting the blood. Next, the adhesive sample in Example 2 was placed in a centrifuge tube, and an appropriate amount of saline was added thereto so that the final concentration of the adhesive sample was 0.1 g / mL. Three parallel samples were prepared. For the negative control group, only 1 mL of saline was added; for the positive control group, 1 mL of distilled water was added; for the experimental group, 1 mL of sample solution was added, and each group had 3 parallel samples. Then, the above centrifuge tubes were placed in a constant temperature water bath at 37°C and incubated for 30 minutes. Except for the blank tube, 0.2 mL of diluted blood was added to each of the remaining tubes and shaken thoroughly. After that, it was incubated at a constant temperature for 60 minutes. During these 60 minutes, the centrifuge tube was turned upside down twice every 30 minutes to ensure that the blood and the material were in full contact. Finally, the centrifuge tube was shaken and centrifuged at 800 g for 5 minutes. The supernatant was taken and added to a 96-well plate, and its absorbance was measured at a wavelength of 545 nm using an ELISA reader.

[0139]

[0140] Results Figure 6 , the results confirmed that the adhesive has good blood compatibility.

[0141] Example 12 (Corneal Adhesion)

[0142] The adhesive prepared in Example 2 was used as an example. A rabbit corneal transplant defect model was used, and the cornea was cut with a 5 mm circular drill. The detached circular cornea was then re-transplanted to the defect site. 100 μL of the adhesive prepared in Example 2 was dropped onto the rabbit corneal wound surface and ultraviolet light (wavelength: 365 nm, intensity: 50 mW / cm 2 ) After 5 seconds of irradiation, the cornea was bonded. The wound healing sites of corneal transplantation were photographed to record the wound healing status of each group.

[0143] Comparative Example 6 (Corneal Adhesion)

[0144] A rabbit corneal transplant defect model was used. After the cornea was cut with a 5mm circular drill, the detached circular cornea was re-transplanted to the defect site. The cornea was sutured with traditional clinical surgical sutures for a total of 8 stitches. The wound healing site of the corneal transplant was photographed to record the wound healing status of each group.

[0145] The results of Example 12 and Comparative Example 6 are shown in Figure 7 The results confirmed that the tissue adhesive prepared in Example 2 had a good healing effect 1 day after surgery, and there was no significant difference from before the corneal defect 10 days after surgery, which was significantly better than the healing effect of traditional surgical suture.

[0146] Example 13 (Conjunctival Adhesion)

[0147] The adhesive prepared in Example 2 was used as an example. A rabbit conjunctival transplant defect model was used, and a scalpel was used to linearly cut the conjunctiva to obtain a linear defect of 5 mm in length. 100 μL of the adhesive was dropped on the surface of the rabbit conjunctival defect and irradiated with ultraviolet light (wavelength: 365 nm, intensity: 50 mW / cm2) for 5 seconds to achieve adhesion of the conjunctival wound surface. The conjunctival wound healing site was photographed to record the wound healing status of each group.

[0148] Comparative Example 7 (Conjunctival Adhesion)

[0149] A rabbit conjunctival transplant defect model was used, and a scalpel was used to linearly cut the conjunctiva to obtain a linear defect of 5 mm in length. The conjunctiva was sutured using traditional clinical surgical sutures, with a total of 6 stitches. The conjunctival wound healing site was photographed to record the wound healing status of each group.

[0150] The results of Example 13 and Comparative Example 7 are shown in Fig. 9 The results confirmed that the tissue adhesive prepared in Example 2 had a good healing effect 1 day after surgery. Ten days after surgery, there was no significant difference from before the conjunctival defect, which was significantly better than the healing effect of traditional surgical sutures.

[0151] For any technician familiar with the art, without departing from the scope of the technical solution of the present invention, the technical content disclosed above can be used to make many possible changes and modifications to the technical solution of the present invention, or modified into equivalent embodiments with equivalent changes. Therefore, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention should still fall within the scope of protection of the technical solution of the present invention.

Claims

1. An ophthalmic hydrogel adhesive which can be rapidly cross-linked in situ, has low swelling and high transparency, characterized in that: The ophthalmic hydrogel adhesive is mainly composed of a hydrophilic polymer and a block polymer, the mass ratio of the hydrophilic polymer to the block polymer is 1:5 to 5:1, the hydrophilic polymer is selected from one of polyethylene glycol and polyvinyl alcohol; the block polymer is poloxamer; the end groups of the hydrophilic polymer and the block polymer are both modified with cross-linking groups, and are covalently connected by the cross-linking groups. The volume percentage of the polymer in the ophthalmic hydrogel adhesive is 1%-30%, preferably 5%-20%.

2. The ophthalmic hydrogel adhesive according to claim 1, characterized in that The transmittance of the ophthalmic hydrogel adhesive is 80-100%, the viscosity of the prepolymerized solution of the ophthalmic hydrogel adhesive is not higher than 60mPa.s, and the penetration depth in the skin tissue is not lower than 100μm; the tissue bonding strength of the ophthalmic hydrogel adhesive after curing is 150-300kPa, and the volume swelling rate is lower than 40%.

3. The ophthalmic hydrogel adhesive according to claim 1, characterized in that The cross-linking groups include acrylate, methacrylate and allyl isocyanate, and the cross-linking of the hydrophilic polymer and the block polymer is achieved through free radical polymerization reaction; the mass ratio of the hydrophilic polymer to the block polymer is 3:7 to 7:

3.

4. The ophthalmic hydrogel adhesive according to claim 1, characterized in that The molecular weight of the polyethylene glycol is 0.2kDa-6kDa, preferably 0.2kDa, 2kDa, 4kDa and 6kDa; the molecular weight of the polyvinyl alcohol is 2kDa-75kDa; the poloxamer is one of F127, F108, F88, F68 and F87, with a molecular weight of 1kDa-30kDa.

5. The method for using the ophthalmic hydrogel adhesive according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) dissolving a hydrophilic polymer having a cross-linking group modified at its terminal group and a block polymer having a cross-linking group modified at its terminal group in an aqueous solution to obtain a 1-50 wt % polymer aqueous solution; (2) When the polymerization is initiated by light-induced crosslinking, a photoinitiator is added to a polymer aqueous solution and mixed evenly to obtain a prepolymer solution. The prepolymer solution is applied to the surface of the tissue to be bonded, and the prepolymer solution is irradiated with light to initiate a crosslinking reaction of the polymer and then solidify, thereby achieving stable adhesion of the tissue; When the polymerization initiation method is chemical cross-linking, a chemical initiator is added to the polymer aqueous solution and mixed evenly to obtain a prepolymer solution. The prepolymer solution is applied to the surface of the tissue to be bonded, and then the polymer in the polymer solution is allowed to cross-link and solidify for 10s-200min to achieve stable adhesion of the tissue.

6. The method of use according to claim 5, characterized in that: The concentration of the polymer aqueous solution in step (1) is 5-50wt%, preferably 5-30wt%.

7. The method of use according to claim 5, characterized in that: The photoinitiator described in step (2) includes lithium phenyl-2,4,6-trimethylbenzoylphosphinate, and the light-induced wavelength range is 200-700nm.

8. The method of use according to claim 5, characterized in that: The chemical initiator described in step (2) includes ammonium persulfate and tetramethylethylenediamine.

9. Use of the ophthalmic hydrogel adhesive according to any one of claims 1 to 4 as a highly transparent ophthalmic tissue adhesive in ocular surface surgery.

10. The use according to claim 9, characterized in that: The ocular surface surgeries include conjunctival wound / transplantation adhesion, corneal wound / transplantation adhesion, retinal wound / transplantation adhesion, and ocular surface wound closure.